Explaining the spread of temporary jobs and its impact on labor turnover - Pierre Cahuc; Olivier Charlot; Franck Malherbet (Institute for the Study of Labor (IZA), 2012)
This paper provides a simple model which explains the choice between permanent and temporary jobs. This model, which incorporates important features of actual employment protection legislations neglected by the economic literature so far, reproduces the main stylized facts about entries into permanent and temporary jobs observed in Continental European countries. We show that the stringency of legal constraints on the termination of permanent jobs has a strong positive impact on the turnover of temporary jobs. We also find that job protection has very small effects on total employment but induces large substitution of temporary jobs for permanent jobs which significantly reduces aggregate production.
urn:nbn:de:101:1-201206146307
Keywords: J63; J64; J68; 330; temporary jobs; employment protection legislation; Befristeter Arbeitsvertrag; Arbeitsmobilität; Arbeitnehmerschutz; Theorie; Europa